Recycle now: learning the 3R of waste management through game-based learning / Nurnasheeba Omar Dani and Noor Suriana Abu Bakar - Omar Dani, Nurnasheeba; Abu Bakar, Noor Suriana (Faculty of Computer and Mathematical Sciences, 2022)
Reduce, reuse and recycle (3R) is the general principle of recycle that used in every country. This general principle helps to keep the environment tidy and clean. However, study is shows that people still lack awareness and knowledge about recycling. Thus, the purpose of this study is to design a 3D role-playing (RPG) for learning 3R, to develop a 3D in game-based learning. This project is use Rapid Application Development (RAD) approach as it is most suitable and provide a fully guideline to develop this game successfully. This game also uses Game-Based Learning Model which is Magic Circle Model. The project game also evaluated based on respondents from Usability Questionnaire that consists of two factor perceived usefulness and perceived ease of use. Findings of this game projects shows 78% of the overall total mean and shows that it has been reached it level of usability of educational computer games in game-based learning. In order to have a better playing experience for the future work, adding more challenging and mission for this game would be a good way to improve the quality of the game.